Genetic determinants of steatosis and fibrosis progression in paediatric non‐alcoholic fatty liver disease. (21st December 2018) - Hudert, Christian A.; Selinski, Silvia; Rudolph, Birgit; Bläker, Hendrik; Loddenkemper, Christoph; Thielhorn, Ria; Berndt, Nikolaus; Golka, Klaus; Cadenas, Cristina; Reinders, Jörg; Henning, Stephan; Bufler, Philip; et al.
Abstract: Background and Aims: Non‐alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in children and adolescents today. In comparison with adult disease, paediatric NAFLD may show a periportal localization, which is associated with advanced fibrosis. This study aimed to assess the role of genetic risk variants for histological disease pattern and severity in childhood NAFLD. Methods: We studied 14 single nucleotide polymorphisms (SNP) in a cohort of 70 adolescents with biopsy‐proven NAFLD. Genotype was compared to an adult control cohort (n = 200) and analysed in relation to histological disease severity and liver tissue proteomics. Results: Three of the 14 SNPs were significantly associated with paediatric NAFLD after FDR adjustment, rs738409 (PNPLA3, P = 2.80 × 10 −06 ), rs1044498 (ENPP1, P = 0.0091) and rs780094 (GCKR, P = 0.0281). The severity of steatosis was critically associated with rs738409 (OR=3.25; 95% CI: 1.72‐6.52, FDR‐adjusted P = 0.0070). The strongest variants associated with severity of fibrosis were rs1260326, rs780094 (both GCKR) and rs659366 (UCP2). PNPLA3 was associated with a portal pattern of steatosis, inflammation and fibrosis. Proteome profiling revealed decreasing levels of GCKR protein with increasing carriage of the rs1260326/rs780094 minor alleles and downregulation of the retinol pathway in rs738409 G/G carriers. Computational metabolic modelling highlighted functional relevance of PNPLA3, GCKR and UCP2 for NAFLD development. Conclusions: This study provides evidence for the role of PNPLA3 as a determinant of portal NAFLD localization and severity of portal fibrosis in children and adolescents, the risk variant being associated with an impaired hepatic retinol metabolism. Abstract : See Editorial on Page440